Phase Ib study of pembrolizumab in combination with trastuzumab emtansine for metastatic HER2-positive breast cancer - Sara M Tolaney; Tianyu Li; Edward T Richardson; Judith Agudo; Elizabeth A Mittendorf; Beth Overmoyer; Eric P Winer; Adrienne G Waks; Tanya E Keenan; Nabihah Tayob; Gerburg M Wulf; Victoria Attaya; et al. (Journal for ImmunoTherapy of Cancer)
Background Preclinical and clinical data support potential synergy between anti-HER2 therapy plus immune checkpoint blockade. The safety and tolerability of trastuzumab emtansine (T-DM1) combined with pembrolizumab is unknown.Methods This was a single-arm phase Ib trial (registration date January 26, 2017) of T-DM1 plus pembrolizumab in metastatic, human epidermal growth factor receptor 2 (HER2)-positive breast cancer. Eligible patients had HER2-positive, metastatic breast cancer previously treated with taxane, trastuzumab, and pertuzumab, and were T-DM1-naïve. A dose de-escalation design was used, with a dose-finding cohort followed by an expansion cohort at the recommended phase 2 dose (RP2D), with mandatory baseline biopsies. The primary endpoint was safety and tolerability. Secondary endpoints included objective response rate (ORR) and progression-free survival (PFS). Immune biomarkers were assessed using histology, protein/RNA expression, and whole exome sequencing. Associations between immune biomarkers and treatment response, and biomarker changes before and during treatment, were explored.Results 20 patients received protocol therapy. There were no dose-limiting toxicities. The RP2D was 3.6 mg/kg T-DM1 every 21 days plus 200 mg pembrolizumab every 21 days. 85% of patients experienced treatment-related adverse events (AEs) ≥grade 2, 20% of patients experienced grade 3 AEs, and no patients experienced grade >4 AEs. Four patients (20%) experienced pneumonitis (three grade 2 events; one grade 3 event). ORR was 20% (95% CI 5.7% to 43.7%), and median PFS was 9.6 months (95% CI 2.8 to 16.0 months). Programmed cell death ligand-1 and tumor infiltrating lymphocytes did not correlate with response in this small cohort.Conclusions T-DM1 plus pembrolizumab was a safe and tolerable regimen. Ongoing trials will define if there is a role for checkpoint inhibition in the management of HER2-positive metastatic breast cancer.Trial registration number NCT03032107.